How acute renal failure led to the diagnosis of aortic coarctation. Issue 3 (12th March 2023) - Kantauskaite, Marta; Fürst, Günter; Minko, Peter; Antoch, Gerald; Rump, Lars Christian; Potthoff, Sebastian Alexander
Abstract : The present case report focuses on a rare presentation of aortic coarctation. A 38-year-old man with well-controlled arterial hypertension, minimal change glomerulonephritis and colitis ulcerosa was suffering from recurrent acute renal failure episodes during viral gastroenteritis. No other symptoms at rest or during physical activity were present. The workup included renal duplex sonography, which unmasked tardus parvus profile in both kidneys without any acceleration of blood flow in the renal arteries. Further examination included CT angiography, which confirmed the diagnosis of aortic coarctation. The observed narrowing of the aorta measured 4 mm and was treated with percutaneous transluminal angioplasty and stent implantation (final diameter 12 mm). After the procedure, the patient had normal blood pressure values without the need of any medication; duplex sonography showed improved renal perfusion. The present case confirms the importance of evaluation for secondary hypertension and thorough workup of acute renal failure in young patients.